Antioxidant and Antistaphylococcal Activity of Topical Fucoidan Gel from Sargassum oligocystum Montagne - Bayuran, Richie (JPAIR Multidisciplinary Research, 2019)
Brown seaweed is one of the algal species that has been used as food, a source of nutritional supplements, and formulated for therapeutic and cosmetic purposes. This study evaluated the antioxidant and antistaphylococcal activities of topical fucoidan gel (TFG) from the Sargassum oligocystum. A completely randomized design was used, and the experimental protocol includes extraction, lyophilization, and characterization, quality testing, and biological assay. Physicochemical tests suggested that the lyophilized fucoidan is comparable with the properties of pharmaceutical-grade fucoidan. FTIR characterization revealed that fucoidan spectra contain the key functional groups, the sulfate groups, and polysaccharide chains. The formulated topical fucoidan gel also conforms to the selected minimum standards conducted for semi-solid preparation. Analysis of variance of antioxidant and antistaphylococcal assays showed that there was a significant difference in the median inhibitory concentration (IC50) and inhibitory zone (IZ) among treatments at the p
Keywords: Applied Science; Antioxidant; Antistaphylococcal; DPPH Assay; Disc Diffusion Method; Philippines